2022
DOI: 10.1007/s00520-022-07073-8
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell transplantation patients receiving a novel oral care protocol for oral mucositis prevention and treatment: patient-reported outcomes and quality of life

Abstract: Background Oral mucositis (OM) is one of the most debilitating effects of toxicity due to hematopoietic stem cell transplantation (HSCT) conditioning regimens. The aim of this secondary analysis of the data of a phase II study designed to assess the efficacy of a novel oral care protocol containing bovine colostrum and aloe vera to prevent oral mucositis was to compare outcomes reported by patients with those collected by healthcare professionals (HCPs). Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…Concordant with this nding, Vale et al observed that 60.7% of patients developed mucositis after SCT, and a preventive regimen could effectively reduce the process of mucositis in these patients (28). Guberti et al also claimed that 78% of SCT patients experienced mucositis, and using the applied protocol reduced the severity of their mucositis and improved their quality of life, which is in agreement with our ndings (29). In a similar study but with a different intervention, Hadid et al found very high mucositis levels in chemotherapy patients in grades 3 and 4, and palifermin could reduce mucositis severity in patients undergoing chemotherapy (30).…”
Section: Discussionsupporting
confidence: 89%
“…Concordant with this nding, Vale et al observed that 60.7% of patients developed mucositis after SCT, and a preventive regimen could effectively reduce the process of mucositis in these patients (28). Guberti et al also claimed that 78% of SCT patients experienced mucositis, and using the applied protocol reduced the severity of their mucositis and improved their quality of life, which is in agreement with our ndings (29). In a similar study but with a different intervention, Hadid et al found very high mucositis levels in chemotherapy patients in grades 3 and 4, and palifermin could reduce mucositis severity in patients undergoing chemotherapy (30).…”
Section: Discussionsupporting
confidence: 89%
“…Pathobiologically, onset of the first phase of OM occurs immediately after starting chemotherapy, and the healing phase usually occurs approximately 2 to 4 weeks after the final day of chemotherapy [18][19][20]. Clinically, the mean onset of OM was 9.1 days after initiation of the conditioning regimen and that the duration was 10.4 days in patients undergoing HSCT [17]. Onset and healing of OM in this study indicated in accordance with these reports.…”
Section: Discussionsupporting
confidence: 87%
“…Vagliano et al [16] reported that 71.4% of patients undergoing HSCT developed OM and that 21.6% had ≥ G3 OM. Guberti et al [17] found that 78.0% of patients who underwent HSCT developed OM. In a systematic review, the incidence of OM in patients undergoing HSCT was 83.5% among seven studies [2].…”
Section: Discussionmentioning
confidence: 99%
“…Vagliano et al [16] reported that 71.4% of patients undergoing HSCT developed OM and that 21.6% had ≥ G3 OM. Guberti et al [17] found that 78.0% of patients who underwent HSCT developed OM. In a systematic review, the incidence of OM in patients undergoing HSCT was 83.5% among seven studies [18].…”
Section: Discussionmentioning
confidence: 99%
“…Pathological onset of the rst phase of OM occurs immediately after starting chemotherapy, and the healing phase usually occurs approximately 2 to 4 weeks after the nal day of chemotherapy [19][20][21]. Guberti et al [17] reported that the mean onset of OM was 9.1 days after initiation of the conditioning regimen and that the duration was 10.4 days in patients undergoing HSCT. Our results are similar to these reports and are considered valid because the cells of the oral cavity usually have a turnover cycle of 7 to 14 days [22].…”
Section: Discussionmentioning
confidence: 99%